An assessment of the social work program in Turkey in terms of labour market experience and professional skill attainment - Bulent Arpat; Mete Kaan Namal; Mustafa Kocanci; Aynur Yumurtaci (Amfiteatru Economic Journal, 2021)
Dominance of theory-based education is not well connected by the current practices. So, the knowledge delivered within higher education institutions cannot create adequate value in the market and in turn which causes the youth unemployment to become a chronicle problem. Therefore, work placement opportunities within higher education create significant advantages during the transition to the labour market. This study aims to evaluate the efficiency of the Social Work Program in Turkey, in which students work at public institutions during their university education to gain experience, professional skills, and knowledge about the labour market. The research makes use of mixed methods and a crosssectional approach. In terms of the research analysis, descriptive and inferential methods, as well as content analysis, are utilized. The findings show that, while the Social Work Program procured remarkable attainments for the students about the labour market, it is mostly inadequate for professional skill-building. The reason, it is determined as a lack of overlap between the students' field of education and their designated work placement. If the program is redesigned according to this approach, it might be predicted to become prominent as an active and robust workplace policy in fighting youth unemployment.
Keywords: E24; R23; J2; J21; 330; youth unemployment; social work program; utility program; professional skills; labour market